Is There a Global Currency War? - Robert W. Włodarczyk (Entrepreneurial Business and Economics Review)
The main aim of this article is to identify factors influencing the direction of change in exchange rates and to assess whether it is justifiable to use the term “currency wars” to describe such activities. The main forms of such “currency wars” in contemporary global economy have been characterized and their impact on financial markets and national economies has been analyzed.